Dataset for Aquaculture Characterization in Kenya - Brako Dompreh, Eric; Manyise, Timothy; Rossignoli, Cristiano (2024)
Data were collected in August 2024 through computer-assisted personal interviews (CAPIs) conducted on mobile tablets. A KoBo-based questionnaire was administered by 38 trained enumerators. Employing a multistage sampling approach, purposive and simple random sampling techniques were utilized to select 5315 farmers across Kenya. This study aimed to understand aquaculture production practices and associated livelihood activities. The collected data encompasses various aspects, including demographics, land ownership, production details, poverty levels, food security, income sources, livestock holdings, climate factors, and gender dynamics.